Antiproliferative activity of whey and casein bioactive peptides on breast cancer: an in vitro and in silico study - AKBAY, TUĞBA (My University, 2022)
Bioactive peptides from milk proteins are dietary components with various biological properties and therapeutic effects in a variety of health conditions, including cancer. In this study, the effects of goat milk proteins and bioactive peptides on the MCF-7 breast cancer cell line were investigated. Milk was separated into casein and Whey fractions and treated with either pepsin or trypsin enzymes. Peptides of the hydrolyzed fractions were identified with LC-QTOFF/MS. After identification, the hydrolyzed Whey and casein fractions were incubated with MCF-7 breast cancer cells at various concentrations. The in vitro cytotoxicity of hydrolyzed fractions against MCF-7 cells was tested using MTT assay and flow cytometry analysis. The dead MCF-7 cells were analyzed with LC-Q-TOF/MS. In dead MCF-7 cells, the pyruvate kinase M2, mucin 1-C, glycogen synthase kinase 3-beta, and L-lactate dehydrogenase B were found to be downregulated in the LC-Q-TOF/MS analysis, while receptor-interacting serine/ threonine-protein kinase 1 was found to be up-regulated. These enzymes and mucin-1C also interacted with the milk-derived bioactive peptides in silico. The goat milk bioactive peptides exhibited high binding affinity with these enzymes and mucin-1C. The 5 mu g mL(-1) trypsin-treated casein fraction caused the highest MCF-7 cell death. In conclusion, the bioactive peptides of the pepsin-treated casein fraction and trypsin-treated Whey fraction of goat milk may inhibit the survival of breast cancer cells and exert their effects via multiple mechanisms. The results of this study are novel, suggesting that goat milk-based specific bioactive peptides may have potential as an anti-tumour agent in the treatment of breast cancer.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Klinik Biyokimya; Kanser Araştırmaları; Moleküler Biyoloji; İlaç Keşfi; Yaşlanma; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Biyokimya; Yapısal Biyoloji; Biochemistry, Genetics and Molecular Biology (miscellaneous); Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Biochemistry; Structural Biology; Goat milk; Casein; Whey proteins; Bioactive peptides; Breast cancer; GOAT MILK; TUMOR; APOPTOSIS; CYTOMETRY; ARGININE; SURFACE; LYSINE; RICH